Efficient and reversible Cas13d-mediated knockdown with an all-in-one lentivirus-vector - Lv, Suli; Zhao, Xuefeng; Ma, Xianyun; Zou, Qingli; Li, Neng; Yan, Yingying; Sun, Lidong; Song, Tanjing (Frontiers in Bioengineering and Biotechnology, 2022)
Type VI CRISPR effector Cas13d from Ruminoccocus flavefaciens XPD3002 (RfxCas13d) is an RNA-guided RNA endonuclease. RfxCas13d has been harnessed to knockdown gene expression with high specificity in various systems including mammalian cells. While inducible knockdown is advantageous over constitutive knockdown in many scenarios, current inducible systems of RfxCas13d express CRISPR RNA and Cas13d separately. Such systems could be cucumber to handle and may hamper the application of RfxCas13d in some scenarios. Here, we design an all-in-one Cas13d lentivirus vector which renders efficient and inducible knockdown in a doxycycline dosage-dependent manner. Furthermore, we find that Cas13d has a short half-life in mammalian cells. As a result, knockdown can be promptly reversed after Doxycycline withdrawal. This vector is particularly useful to study indispensable genes and/or in cells hard to transduce.